Estilo de liderazgo predominante en los docentes del nivel primaria de instituciones educativas Red N° 08 Región Callao - Matos Villanueva, Jesús Martín (2010)
The research identifies the predominant leadership style of teachers of primary schools in the Callao Region. We chose a descriptive simple type transversal research, quantitative in nature. In order to do this we used the Leadership Style Questionnaire (Celide - A), Morales-Molero, which reflects the typology presented by Bernard Bass, who considers three styles of leadership. This test allows a score for each of the three styles and dimensions that comprise it. We determined a random sample of 119 people, for the universe of 168 teachers from 9 schools. The study group was composed of 168 teachers from 9 schools, and identified a random sample of 119 people. The results show that the vast majority of teachers focuses on transformational leadership style.